International tourists’ visual preferences of Kuala Lumpur historic city centre - Najd, Meysam Deghati (2014)
Rapid developments in Malaysia have resulted into unrestrained urban growth in major cities, particularly in Kuala Lumpur, the capital city. Urbanization also led to the deterioration of the Kuala Lumpur historic urban areas and their domination by modern urban constructions. Through these changes, city transformation witnesses identity crises in addition to the formation of an identical modern global image of city. In this regards, tourism industry is also affected due to historic heritage conservation issues. Therefore, serious attempts are highly demanded to implement an integrated heritage conservation by utilizing public participation while elevating the tourism industry. This study aims to identify public perceptions towards historic urban areas by bringing in public and international tourists’ perception into account for a sustainable and integrated heritage conservation. The Kuala Lumpur Historic City Centre (KLHCC), the most historic urban heritage site in the city was taken as the study area for the current research. An exploratory preference survey carried out by using a photo questionnaire that sampled 308 international tourists from 54 countries while visiting the study area. The data was analysed by means of the Content Identifying Method (CIM) and several statistical analyses to determine group preferences toward KLHCC, the historic urban area. The findings of this study showed low preferability of KLHCC as a prominent historic area in the eyes of international tourists despite of ongoing heritage conservation by the government. It also indicated a deficiency of existing expert-based conservation guidelines, rules and regulations. Moreover, the findings introduced six key visual preference dimensions of historic urban area which significantly contribute to the international tourists’ preferences. Chaotic, historic architecture, roadside heritage, greenery, connectivity and modernity are those dimensions from which historic architecture was measured as the most preferred while chaotic was of the least preferred among others. In addition to the physical characteristics, the influences of some personal factors were studied against visual preference dimensions. These factors included of socio-demographic characteristics of gender, age, level of education and country of origin together with socio-psychological motivation, level of familiarity and interest level. Contrary to the socio-demographic characteristics of participants that did not show any significant impact upon their visual preferences toward KLHCC, socio-psychological motivation, level of familiarity and interest level were highly correlated and impose influences on the dimension groups. Implementations of the findings from this study have the capability of contributing towards public-based conservation and preservation of historic urban areas in different levels of consideration and decision making processes.